A dimensional approach to affective disorder: The relations between Scl-90 subdimensions and QEEG parameters - Kesebir, Sermin; Yosmaoglu, Ahmet; Tarhan, Nevzat (Frontiers in Psychiatry, 2022)
Objectives: QEEG reflects neuronal activity directly rather than using indirect parameters such as blood deoxygenation and glucose utilization as in fMRI and PET. The correlation between QEEG spectral power density and Symptom Check List-90-R may help identify biomarkers pertaining to brain function, associated with affective disorder symptoms. This study aims at determining whether there is a relation between QEEG spectral power density and Symptom Check List-90-R symptom scores in affective disorders. Methods: This study evaluates 363 patients who were referred for the initial application and diagnosed with affective disorders according to DSM-V, with QEEG and Scl-90-R. Spectral power density was calculated for the 18 electrodes representing brain regions. Results: Somatization scores were found to be correlated with Pz and O1 theta, O1 and O2 high beta. Whereas FP1 delta activities were correlated with anxiety, F3, F4 and Pz theta were correlated with obsession scores. Interpersonal sensitivity scores were found to be correlated with F4 delta, P3, T5, P4, T6 alpha and T5 and T6 theta activities. While depression scores were correlated with P3 and T4 delta, and T4 theta, there was a correlation between anger and F4 and T4 alpha and F8 high beta activities. Paranoia scores are correlated with FP1, F7, T6 and F8 theta, T5 and F8 delta, and O2 high beta activities. Conclusions: According to our results, anxiety, obsession, interpersonal sensitivity, depression, anger, and paranoia are related with some spectral powers of QEEG. Delta-beta coupling seems to be a neural biomarker for affective dysregulation.